The Influence of Multimedia Use and Sermon Themes on the Spirituality of Christian Adolescents - Kaurouw, Bryan Christian; Supit, Sugijanti; Siang, Jhoni Lagun (Peneliti.net, 2024)
This study aims to determine the influence of the multimedia utilization and sermon themes on the spirituality of Christian adolescents at GMIM Sentrum Airmadidi. This study uses a quantitative approach with a survey method. The sampling technique used is probability sampling with purposive sampling. The findings showed that there was an influence of Multimedia Utilization (X1) on Christian Adolescent Spirituality (Y). This is based on the results of the t-test which states that the t-count value is 2,138 ≥ 2,042, while the significance value is 0.040 ≤ 0.05. However, the influence of Multimedia Utilization on Christian Adolescent Spirituality is negative. This can be seen from the regression equation Y = 44.833 + -0.94, meaning that for every 1% increase in the value of the variable, the value of the Christian Adolescent Spirituality variable will decrease by 0.94. Other test results also showed that there was an influence of the Sermon Theme (X2) on the Spirituality of Christian Adolescents (Y). This is evidenced by the results of the t-test which shows that the t-count value is 3.784 ≥ 2.042, while the significance value is 0.001 ≤ 0.05, with the regression equation Y = 44.833 + 0.643 (positive effect). This means that for every 1% increase in the value of the Sermon Theme, the value of the Christian Adolescemt Spirituality will increase by 0.643. Other findings also stated that based on the results of the f-test, it was found that the f-count value was 7.047 ≥ 3.32, while the significance value was 0.003 ≤ 0.05, this shows that the variables of Multimedia Utilization and Sermon Theme together have a positive and significant effect on the variable of Christian Adolescent Spirituality. The magnitude of the influence is 0.320 or 32%. While the remaining 68% was influenced by other factors that were not studied.